Analysis of The Decrease in Sign and Symptoms of Hallucinations with The Application of Aerobic Exercise Physical Activity Therapy - Armayanti, Millen Novia (STIKes RSPAD RSPAD Gatot Soebroto, 2023)
Schizophrenia is a mental disorder that can cause sufferers to experience deviations in thoughts, perceptions, emotions and behavior. People with schizophrenia can experience delusions or hallucinations. Hallucination are one of the positive symptoms of schizophrenia, people with schizophrenia who experience hallucinations can hear voices or see things that are not real. The aim of this scientific work is to provide an overview regarding the application of nursing care to patients with hallucinations through physical activity used is aerobic exercise. The client named Mr. F is 28 years old who experiences visual and auditory hallucinations. The nursing actions given to control hallucinations are based on the standards of nursing care that have been set for the client is generalist nursing interventions for 1 days and continued with aerobic exercise physical activity therapy as a distraction technique for 11 days. The results of the application of aerobic exercise physical activity distraction therapy showed a decrease in signs of hallucinations from a score of 19 to a score of 8. Aerobic exercise therapy can be applied as an innovative nursing action to control hallucinations in providing nursing care in hospitals,